Gain recovery dynamics in active type-II semiconductor heterostructures - Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Meier, T.; Hader, J.; Moloney, J. V.; et al. (My University, 2023)
Type-II heterostructures as active layers for semiconductor laser devices combine the advantages of a spectrally broad, temperature stable, and efficient gain with the potential for electrical injection pumping. Their intrinsic charge carrier relaxation dynamics limit the maximum achievable repetition rates beyond any constraints of cavity design or heat dissipation. Of particular interest are the initial build up of gain after high-energy injection and the gain recovery dynamics following depletion through a stimulated emission process. The latter simulates the operation condition of a pulsed laser or semiconductor optical amplifier. An optical pump pulse injects hot charge carriers that eventually build up broad spectral gain in a model (Ga,In)As/GaAs/Ga(As,Sb) heterostructure. The surplus energies of the optical pump mimic the electron energies typical for electrical injection. Subsequently, a second laser pulse tuned to the broad spectral gain region depletes the population inversion through stimulated emission. The spectrally resolved nonlinear transmission dynamics reveal gain recovery times as fast as 5 ps. These data define the intrinsic limit for the highest laser repetition rate possible with this material system in the range of 100 GHz. The experimental results are analyzed using a microscopic many-body theory identifying the origins of the broad gain spectrum.
Keywords: ddc:530